The Realization of a Control Algorithm and its PLC Based Program Able to Authorize Four Different Ranks of Priority to Elevator Users - Mümine Yıldız Coşkun; Mehmet KARALI (International Journal of Applied Methods in Electronics and Computers, 2016)
Elevator software programs are currently unable to meet the required demand regarding elevator services of high-rise community and government buildings such as hospitals and social centers. Administrators, emergency room doctors and nurses in hospitals; authorities in public or governmental buildings (such as ministers, governors, rectors, deans); or managers, and staff working in community buildings wish privileged use of existing elevators. This isn’t only a personal privileged, but an institutional necessity; resulting in a second elevator assigned to VIP use. Regrettably, while such elevators are empty, others become too crowded and queues form up, resulting in frequent breakdowns. Not to mention the unauthorized use of said elevators causing problems in instances where an emergency is at hand. The solution of card and/or key systems on the other hand has become tedious and inefficient. In this project, authorization rankings were assigned and special usage privileges given. Thus, in cases where VIP usage is needed, the elevator temporarily cancels out either totally or partially all other calls according to VIP ranking, resulting in the efficient use of elevators by preventing them from being inactive when there is no ongoing VIP usage. Algorithms have been written for authorized use and have been designed for flexible response using PLCs. This project utilizes a model encompassing a four rank authorization system (three VIP, and one normal) which, after a number of simulations, has been tested on a servomotor-powered mechanism. The project is planned to be expanded to incorporate up to a ten rank authorization system.